Kinetic studies on gold nanoparticle formation in aqueous medium - Chakraborty, A. (Trans Tech Publications Ltd, 2014)
Extensive research data were published in the last decade on synthesis, characterization and application of AuNP for drug delivery and protein conjugation. Gold nanoparticles were synthesized by the well-known citrate reduction (Turkevitch) method. Precursor concentrations were measured by UV-Vis spectroscopy and iodometric estimation methods. During reaction surface plasmon resonance (SPR) peaks of the reaction medium decreased from 556.5 nm to 527.2 nm in about 300s. Experimental data on time-concentration profiles of the precursor in the reaction medium were used to calculate pseudo-first order rate constant (0.0178Â± 0.002 s-1). Atomic Force Microscopy (AFM) was used for morphological characterization of the nanoparticles. Â© 2014 Trans Tech Publications, Switzerland.